Undergraduate Students’ English Pronunciation Anxiety (EPA) In Pronunciation Class at English Education Department Wiralodra University - Wati, Atikah; Efendi, Nasori; Anggrarini, Natalia; Fauziah, Ade fitri (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
One of the difficulties faced by non-native speakers when learning English is pronouncing sounds or words. In this case, there are many kinds of factors or problems. One of them is the feeling of anxiety when speaking English. One of them is English pronunciation anxiety. The purpose of this study is to determine the level of English Pronunciation Anxiety (EPA) of undergraduate students. The second is to determine the indicators of English Pronunciation Anxiety (EPA) of undergraduate students in pronunciation classes. This study used qualitative method and case study as a research design. The participation of this study of second-semester students in the 2022/2023 academic year, with 18 students. Overall, The researcher examined students' anxiety levels in English pronunciation, identifying two levels: "mild" and "moderate." Eight students experienced "mild" anxiety, while ten experienced "moderate" anxiety. The moderate level of anxiety indicated significant anxiety and self-consciousness. The higher scores indicated a higher level of concern about their pronunciation, reflecting a more substantial anxiety and respect for their ability. The study found that undergraduate students at Wiralodra University experienced moderate to high levels of English pronunciation anxiety. This anxiety was attributed to self-consciousness and concern about their pronunciation abilities. The research suggests that educators can use relaxation techniques, constructive feedback, and language-focused activities to manage anxiety. Curriculum developers should incorporate pronunciation-focused activities and improve teacher training programs. Further research is needed to explore the impact of cultural, linguistic, and educational backgrounds on pronunciation anxiety.